resin film

JP2026165123APending Publication Date: 2026-10-13KANEKA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2026053736
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-28
Filing Date
2026-03-27
Publication Date
2026-10-13

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、0℃~60℃の全域で耐衝撃性に優れる樹脂フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165123000001
    Figure 2026165123000001
Patent Text Reader

Abstract

We provide a resin film that exhibits excellent impact resistance across the entire temperature range from 0°C to 60°C. [Solution] A resin film with a thickness of 150 μm, in which dynamic viscoelasticity measurements are performed in tensile mode at a vibration frequency of 100 Hz and a temperature range of 0°C to 60°C, and the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C is all 0.2 or greater. The resin film preferably has a haze of 0.01% to 2.0%. The resin film is suitable for use as a front panel for foldable devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin film.

Background Art

[0002] In recent years, foldable display panels that can be repeatedly folded have been proposed for smartphones and tablet terminals to achieve both larger screens and portability. Foldable display panels are required to be capable of repeated deformation between a bent shape and a flat non-bent shape. In such display panels, repeated stress concentration occurs at the folded portion, and as a result, there are problems that the front plate may be damaged, the display itself may be damaged and stop displaying, or the impact when dropped or when writing with a stylus pen is transmitted to the inside and affects the display itself.

[0003] For example, Patent Documents 1 and 2 disclose, as an impact-resistant film for use in front plates of foldable devices, a film using an acrylic block copolymer containing a polymer block composed of structural units derived from methacrylic acid ester as a base resin.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0005] However, the film composed of the base resin alone disclosed in Patent Documents 1 and 2 has a problem that the impact resistance is not sufficient over the entire assumed use temperature range of 0°C to 60°C for the film.

[0006] This invention has been made in view of the above problems, and aims to provide a resin film that exhibits excellent impact resistance over the entire temperature range from 0°C to 60°C. [Means for solving the problem]

[0007] The inventors of the present invention have discovered that the above problems can be solved by using a resin film formed from a resin composition containing specific additives, and have completed the present invention.

[0008] This disclosure relates to the following resin films.

[0009] [1] A resin film with a thickness of 150 μm, in which dynamic viscoelasticity measurements are performed in tensile mode at a vibration frequency of 100 Hz and a temperature range of 0°C to 60°C, and the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C is all 0.2 or greater. [2] The resin film described in [1], wherein the haze is 0.01% or more and 2.0% or less. [3] A resin film as described in [1] or [2], for use in foldable devices. [Effects of the Invention]

[0010] According to the present invention, it is possible to provide a resin film that exhibits excellent impact resistance across the entire temperature range from 0°C to 60°C. [Modes for carrying out the invention]

[0011] ≪Resin film≫ The resin film of this embodiment has the characteristic that, when a dynamic viscoelasticity measurement is performed in tensile mode on a resin film with a thickness of 150 μm at a vibration frequency of 100 Hz and a temperature range of 0°C to 60°C, the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C is all 0.2 or greater.

[0012] According to the resin film of this embodiment, when dynamic viscoelasticity measurements are performed in tensile mode in the range of 0°C to 60°C, the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C is all 0.2 or higher, thus providing the effect of excellent impact resistance across the entire range of 0°C to 60°C.

[0013] <Loss tangent (tanδ)> The tanδ of a resin film is one indicator of its impact resistance; a larger tanδ means the film has superior impact resistance. The tanδ values ​​at 0°C, 25°C, 40°C, and 60°C represent indicators of the film's impact resistance at expected operating temperatures ranging from low to high. A tanδ of 0.2 or higher at all four of these temperatures indicates superior impact resistance across the entire temperature range from 0°C to 60°C. When dynamic viscoelasticity measurements were performed in tensile mode on a resin film with a thickness of 150 μm at a vibration frequency of 100 Hz and a temperature range of 0°C to 60°C, the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C was all 0.2 or greater, preferably between 0.24 and 0.6, more preferably between 0.28 and 0.6, and even more preferably between 0.32 and 0.6.

[0014] When dynamic viscoelasticity measurements were performed in tensile mode on a resin film with a thickness of 150 μm at a vibration frequency of 100 Hz and a temperature range of 0°C to 60°C, the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C was all 0.2 or greater, and of the four data points, preferably one or more, more preferably two or more, even more preferably three or more, and even more preferably four, were 0.25 or greater. For a resin film with a thickness of 150 μm, when dynamic viscoelasticity measurements were performed in tensile mode at a vibration frequency of 100 Hz and a temperature range of 0°C to 60°C, the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C was all 0.2 or higher, and of the four data points, preferably one or more, more preferably two or more, even more preferably three or more, and even more preferably four, had a loss tangent of 0.30 or higher. For a resin film with a thickness of 150 μm, when dynamic viscoelasticity measurements were performed in tensile mode at a vibration frequency of 100 Hz and a temperature range of 0°C to 60°C, the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C was all 0.2 or higher, and of the four data points, preferably one or more, more preferably two or more, even more preferably three or more, and even more preferably four, had a loss tangent of 0.35 or higher. The above-mentioned "resin film with a thickness of 150 μm" refers to the thickness of the resin film used when measuring the loss tangent (tanδ). As will be described later, the thickness of the resin film in this embodiment is not particularly limited, but is preferably within the range of 15 μm to 300 μm.

[0015] <Hayes> For a resin film with a thickness of 150 μm, the haze of the resin film is preferably 0.01% to 2.0%, more preferably 0.01% to 1.5%, more preferably 0.01% to 1.0%, and even more preferably 0.01% to 0.9% from the viewpoint of excellent transparency. The haze is measured using a haze meter. The "resin film with a thickness of 150 μm" mentioned above refers to the thickness of the resin film used when measuring haze. As will be described later, the thickness of the resin film in this embodiment is not particularly limited, but is preferably in the range of 15 μm to 300 μm.

[0016] The thickness of the resin film is preferably in the range of 15 μm to 300 μm, more preferably 20 μm to 200 μm, and particularly preferably 25 μm to 150 μm. If the thickness of the resin film exceeds 300 μm, the stress generated at the bending portion becomes large, which is undesirable. Also, if the thickness of the resin film is less than 15 μm, the film may become difficult to handle.

[0017] <Application> As described above, the resin film is excellent in impact resistance over the entire range of 0°C to 60°C. In a preferred embodiment of the resin film, it is also excellent in transparency. For this reason, the resin film can be suitably used for foldable devices.

[0018] <Resin Composition> The resin film is formed from a resin composition. The resin composition preferably contains an acrylic block copolymer (A) and an additive. Hereinafter, the resin composition will be described.

[0019] (Acrylic Block Copolymer (A)) The acrylic block copolymer (A) preferably includes a polymer block (a1) composed of structural units derived from a methacrylic acid ester.

[0020] Examples of the structural unit derived from a methacrylic acid ester (hereinafter also simply referred to as "methacrylic acid ester unit") include methacrylic acid units, methyl methacrylate units; ethyl methacrylate units; propyl methacrylate units such as n-propyl methacrylate units and iso-propyl methacrylate units; butyl methacrylate units such as n-butyl methacrylate units, iso-butyl methacrylate units, sec-butyl methacrylate units and tert-butyl methacrylate units; pentyl methacrylate units; hexyl methacrylate units; cyclohexyl methacrylate units; heptyl methacrylate units; octyl methacrylate units such as n-octyl methacrylate units and 2-ethylhexyl methacrylate units; nonyl methacrylate units; decyl methacrylate units; undecyl methacrylate units; dodecyl methacrylate units; tridecyl methacrylate units; tetradecyl methacrylate units; hexadecyl methacrylate units; octadecyl methacrylate units; alkyl methacrylate units such as icosyl methacrylate units, and the like. Among these, a homopolymer or copolymer composed of a monomer such as a methyl methacrylate unit is preferred, and a homopolymer or copolymer composed of a methyl methacrylate unit monomer is particularly preferred.

[0021] Examples of acrylic block copolymers (A) include copolymers in which the polymer block (a1) contains structural units derived from methacrylic acid ester, and other structural units include structural units derived from acrylonitrile, structural units derived from ethylene, or structural units derived from acrylic acid ester. Among these, structural units derived from acrylic acid ester are preferred.

[0022] Examples of constituent units derived from acrylic acid esters (hereinafter also simply referred to as "acrylic acid ester units") include acrylic acid units, methyl acrylate units, ethyl acrylate units, propyl acrylate units such as n-propyl acrylate units and iso-propyl acrylate units, butyl acrylate units such as n-butyl acrylate units, iso-butyl acrylate units, sec-butyl acrylate units and tert-butyl acrylate units, pentyl acrylate units, hexyl acrylate units, cyclohexyl acrylate units, heptyl acrylate units, octyl acrylate units such as n-octyl acrylate units and 2-ethylhexyl acrylate units, nonyl acrylate units, decyl acrylate units, undecyl acrylate units, dodecyl acrylate units, tridecyl acrylate units, tetradecyl acrylate units, hexadecyl acrylate units, octadecyl acrylate units, and alkyl acrylate units such as eicosyl acrylate units. Among these, homopolymers or copolymers consisting of monomers such as n-butyl acrylate units and 2-ethylhexyl acrylate units are preferred, and homopolymers or copolymers consisting of n-butyl acrylate units are particularly preferred.

[0023] In the following, polymer blocks containing constituent units derived from acrylic acid esters will also be referred to as "polymer blocks consisting of constituent units derived from acrylic acid esters (a2)".

[0024] From the viewpoint of the resulting film having excellent impact resistance, the content of the polymer block (a1) is preferably 20% to 50% by weight, more preferably 30% to 49% by weight, even more preferably 35% to 48% by weight, and still more preferably 37% to 46% by weight, based on the total weight of the acrylic block copolymer (A). Furthermore, the acrylic block copolymer (A) may be a mixture of several acrylic block copolymers (A) having different polymer block (a1) content, and by mixing these, the polymer block (a1) content can be adjusted to the above range.

[0025] The acrylic block copolymer (A) preferably contains a polymer block (a1) consisting of structural units derived from methacrylic acid ester and a polymer block (a2) consisting of structural units derived from acrylic acid ester. The weight ratio (a1) / (a2) of polymer block (a1) to polymer block (a2) is preferably 20 / 80 to 50 / 50, more preferably 30 / 70 to 49 / 51, even more preferably 35 / 65 to 48 / 52, and even more preferably 37 / 63 to 46 / 54.

[0026] The acrylic block copolymer (A) is preferably a triblock copolymer consisting of polymer block (a1)-polymer block (a2)-polymer block (a1), or a diblock copolymer consisting of polymer block (a1)-polymer block (a2). Of these, the triblock copolymer is more preferred.

[0027] The acrylic block copolymer (A) preferably has a Shore A hardness of 50 to 100 as measured in accordance with ISO 7619-1. From the viewpoint of achieving an excellent balance between impact resistance and hardness of the resin film, the Shore A hardness is preferably 55 to 90, more preferably 60 to 85, and even more preferably 65 to 80.

[0028] Examples of commercially available acrylic block copolymers (A) include Kuraray's Clarity LA2250, LA2140, LA2330, LA2550, LA2270, LA4285, LA3250, LA3320, LK9243, KL-LK9333, LA1892, LB550, and Arkema's NanoStrength M22, M22N, M51, D51N, M52, M52N, M53, M55, M65, M65N, M75, M75N.

[0029] <Additives> The resin composition contains, in addition to the aforementioned acrylic block copolymer (A), a styrene resin (B) and / or a phenolic compound (C) as additives. The above additives have good compatibility with the acrylic block copolymer (A). By using a resin composition containing the acrylic block copolymer (A) and the above additives, the impact resistance of the film is improved while maintaining the transparency of the resin film, compared to when the acrylic block copolymer (A) is used alone.

[0030] In a resin composition containing an acrylic block copolymer (A) and the above-mentioned additives, the acrylic block copolymer (A) preferably includes polymer blocks (a1) consisting of constituent units derived from methacrylic acid ester, as described above, and the content of the polymer blocks (a1) is preferably 20% by weight or more and 50% by weight or less of the total weight of the acrylic block copolymer (A). Hereinafter, a resin composition containing the acrylic block copolymer (A) and a styrene resin (B) will be referred to as "Resin Composition I", a resin composition containing the acrylic block copolymer (A) and a phenolic compound (C) will be referred to as "Resin Composition II", and a resin composition containing the acrylic block copolymer (A), a styrene resin (B), and a phenolic compound (C) will be referred to as "Resin Composition III".

[0031] (Styrene resin (B)) The weight-average molecular weight of the styrene resin (B) is preferably 700 or more and less than 4000, more preferably 800 or more and 3000 or less, even more preferably 900 or more and 2500 or less, and even more preferably 1000 or more and 2200 or less, from the viewpoint of the resulting film having excellent impact resistance, transparency, and bleed-out resistance.

[0032] The styrene-based resin (B) is preferably at least one selected from the group consisting of styrene-aromatic hydrocarbon copolymers, styrene-aliphatic hydrocarbon copolymers, styrene-(α-methylstyrene)-aliphatic hydrocarbon copolymers, styrene homopolymers, α-methylstyrene homopolymers, and styrene-(α-methylstyrene) copolymers.

[0033] As styrene-aromatic hydrocarbon copolymers, FMR-0150 (softening point 145°C, manufactured by Mitsui Chemicals, Inc.) can be used. As styrene-aliphatic hydrocarbon copolymers, FTR-6100 (manufactured by Mitsui Chemicals, Inc.), FTR-6110 (manufactured by Mitsui Chemicals, Inc.), FTR-6125 (manufactured by Mitsui Chemicals, Inc.), etc. can be used. As styrene-(α-methylstyrene)-aliphatic hydrocarbon copolymers, FTR-7100 (manufactured by Mitsui Chemicals, Inc.), etc. can be used. As styrene homopolymers (or styrene-based polymers), FTR-8120 (manufactured by Mitsui Chemicals, Inc.), etc. can be used. As α-methylstyrene homopolymers (or α-methylstyrene-based polymers), FTR-0100 (manufactured by Mitsui Chemicals, Inc.), etc. can be used. Examples of styrene-(α-methylstyrene) copolymers that can be used include FTR-2120 (manufactured by Mitsui Chemicals), FTR-2140 (manufactured by Mitsui Chemicals), Kristalex1120 (manufactured by Eastman Chemicals), Kristalex3070 (manufactured by Eastman Chemicals), Kristalex3085 (manufactured by Eastman Chemicals), and Kristalex3100 (manufactured by Eastman Chemicals).

[0034] (Phenol compounds (C)) As the phenolic compound (C), a wide range of phenolic antioxidants that are added as stabilizers to various polymers, lubricants, oils, etc., can be used. The phenolic antioxidant may be a hindered phenolic compound, or it may be a phenolic compound that does not fall under the category of a hindered phenolic compound.

[0035] The molecular weight of the phenolic compound (C) is preferably 500 to 1500, more preferably 600 to 1500, and even more preferably 700 to 1500, from the viewpoint of the resulting resin film having excellent impact resistance, transparency, and bleed-out resistance.

[0036] Examples of phenolic compounds (C) include ADEKA STAB A-20, A-30, A-50, A-60, A-80, and A-330 (all manufactured by ADEKA), as well as Irganox 1010, Irganox 1010FF, Irganox 1035, Irganox 1035FF, Irganox 1076, Irganox 1076FD, Irganox 1098, Irganox 245, Irganox 245FF, Irganox 259, and Irganox 3114 (all manufactured by BASF), which can be used alone or in combination.

[0037] (Content of additives) In resin composition I, the content of styrene resin (B) is preferably 10% to 30% by weight, more preferably 13% to 30% by weight, and even more preferably 16% to 30% by weight, based on the total weight of the acrylic block copolymer (A) and the styrene resin (B).

[0038] In resin composition II, the content of phenolic compound (C) is preferably 10% to 30% by weight, more preferably 13% to 30% by weight, and even more preferably 16% to 30% by weight, based on the total weight of the acrylic block copolymer (A) and the phenolic compound (C).

[0039] In resin composition III, the total content of styrene resin (B) and phenolic compound (C) is preferably 10% to 30% by weight, more preferably 13% to 30% by weight, and even more preferably 16% to 30% by weight, based on the total weight of the acrylic block copolymer (A), styrene resin (B), and phenolic compound (C). The styrene resin (B) and phenolic compound (C) have different dependences on the tanδ value with respect to temperature; one tends to decrease in tanδ value with increasing temperature, while the other tends to increase. By using them in combination, a high tanδ value can be maintained over a wide temperature range.

[0040] (Other ingredients) The resin composition may contain components other than the acrylic block copolymer (A), styrene resin (B), and phenolic compound (C) (hereinafter also referred to as "other components"), as long as the effects of the present invention are not impaired. Examples of other components include lubricants, nucleating agents, ultraviolet absorbers, light stabilizers, flame retardants, stabilizers, antistatic agents, plasticizers, crosslinking agents, crosslinking aids, photosensitizers, tackifiers, pigments, dyes, organic fillers, inorganic fillers, silane coupling agents, titanium coupling agents, and other additives, polymerizable group-containing compounds, polymerization initiators, and the like. These other components may be used individually or in combination of two or more.

[0041] <Manufacturing method for resin film> The resin film may be manufactured using either the melt extrusion method or the solution casting method. When manufacturing using the solution casting method, for example, the process includes the steps of preparing a dope by dissolving the resin composition in an organic solvent, casting the dope onto a PET film, then casting the coating solution in a uniform film shape using a bar coater or comma coater so that the thickness after drying is approximately 15 μm to 300 μm, and then drying the coating film. [Examples]

[0042] The present invention will be described more specifically below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0043] <Ingredients> In the examples and comparative examples, the following A1 to A10 were used as the base resin. A1: Acrylic block copolymer (manufactured by Kuraray Co., Ltd., Clarity 2270, MMA ratio 38% by weight, Shore A hardness 71) A2: Acrylic block copolymer (manufactured by Kuraray Co., Ltd., Clarity 4285, MMA ratio 50% by weight, Shore A hardness 95) A3: Acrylic block copolymer (Kuraray Co., Ltd., Clarity LB550, MMA ratio 40% by weight, Shore A hardness 78) A4: Acrylic block copolymer (Kuraray Co., Ltd., Clarity 2330, MMA ratio 20% by weight, Shore A hardness 32) A5: Hydrogenated styrene-based thermoplastic elastomer (Kuraray Co., Ltd., Septon 2002, Shore A hardness 80) A6: Hydrogenated styrene-based thermoplastic elastomer (Kuraray Co., Ltd., Septon 2140) A7: Hydrogenated styrene-based thermoplastic elastomer (Kuraray Co., Ltd., Septon 2104, Shore A hardness 98) A8: Thermoplastic polyester elastomer (manufactured by Toray Celanese, Hytrel 4057) A9: Thermoplastic polyurethane (Pandex T8195, manufactured by DIC Covestropolymer Corporation) A10: Thermoplastic polyurethane (Desmopan 88385, manufactured by DIC Covestropolymer Corporation) A11: Acrylic block copolymer (manufactured by Kuraray Co., Ltd., Clarity 2250, MMA ratio 30% by weight, Shore A hardness 65) A12: Acrylic block copolymer (Arkema, Nano Strength M65, MMA ratio 40% by weight, Shore A hardness 55) *The "MMA ratio" for A1, A2, A4, and A11-A12 indicates the content of polymer blocks consisting of methyl methacrylate units relative to the total weight of each base resin.

[0044] In the examples and comparative examples, the following additives B1 to B10 were used. B1: Low molecular weight polystyrene (manufactured by Sanyo Chemical Industries, Ltd., Hymer ST95, weight-average molecular weight: 4000) B2: Styrene resin (manufactured by Mitsui Chemicals, FTR8120, weight-average molecular weight: 1420) B3: Styrene resin (manufactured by Mitsui Chemicals, FTR6125, weight-average molecular weight: 1950) B4: Styrene resin (manufactured by Mitsui Chemicals, FMR0150, weight-average molecular weight: 1190) B5: Polyethylene glycol (manufactured by Fujifilm & Wako Pure Chemical Industries, Ltd., PEG4000, weight-average molecular weight: 2700-3300) B6: Acrylic copolymer (manufactured by Mitsubishi Gas Chemical Company, OPTIMAS) B7: Phenolic compound (ADEKA Corporation, AO-60, molecular weight: 1178) B8: Phenolic compound (ADEKA Corporation, AO-80, molecular weight: 741) B9: Phenolic compound (ADEKA Corporation, AO-20, molecular weight: 784) B10: Benzotriazole compound (BASF Japan, Tinuvin 329, molecular weight: 329)

[0045] <Doping test> Base resins A1-A12 and additives B1-B10 were weighed to the weights listed in Table 1 and placed in glass bottles. Methylene chloride was added to a solid content concentration of 35 wt% to prepare the dope. A stirring bar was placed in the resulting dope and stirred at 300 rpm for 30 minutes at room temperature using a magnetic stirrer. After standing for 30 minutes, the dope was visually observed and evaluated based on the following criteria. (Evaluation Criteria) ○: No insoluble material was found, and a transparent dope was observed. ×: Insoluble material was observed, and opaque doping was observed.

[0046] Based on the doping test and DMA evaluation, the following resin films were fabricated for the base resins A1-A4, A6-A7, A9-A12 and additives B1-B5, B7-B10, which yielded favorable results, and their film properties were measured.

[0047] <Resin film manufacturing> (Example 1) A mixture of 80% by weight of base resin A1 and 20% by weight of additive B2 was dissolved in methylene chloride to prepare a 35 wt% dope. The prepared dope was cast onto a biaxially oriented polyethylene terephthalate film (Therapyel® PJ101 (manufactured by Toray Industries, Inc.), hereinafter referred to as PET film), and the coating solution was then applied uniformly to a film with a bar coater so that the thickness after drying was approximately 150 μm. The film was laid on a support and baked in a 60°C oven for 5 minutes. Subsequently, it was peeled off the support, fixed to a metal frame on all four sides with tape, and dried at 80°C for 5 minutes and then at 100°C for 5 minutes to obtain a resin film with a thickness of approximately 150 μm.

[0048] (Examples 2-8, Comparative Examples 1-24) A resin film was prepared using the same method as in Example 1, except that the type of base resin and additives, and their content, were changed to those listed in Table 1.

[0049] <Rating> (loss tangent (tanδ)) For each of the obtained resin films, the loss tangent (tanδ) was measured in tensile mode at 100 Hz, -40°C to 120°C using a dynamic viscoelasticity analyzer (DMS6100, manufactured by SII Nanotechnology Co., Ltd.), and the arithmetic mean of the loss tangent (tanδ) at each temperature of 0°C, 25°C, 40°C, and 60°C was calculated. The measurement conditions are shown below. Sample: Width 9mm, distance between gripping parts 20mm Measurement temperature range: -40℃ to 120℃ Heating rate: 3°C / min Atmosphere: The atmosphere is low. Distortion amplitude: 30 μm Measurement frequency: 100Hz Minimum tension / compression force: 100mN Tension / compression gain: 1.5 Initial force amplitude: 100mN~300mN

[0050] (Hayes) Each of the obtained resin films was measured using a haze meter (HAZEMETER HM-150N, manufactured by Murakami Color Technology Laboratory) in accordance with JIS-K-7361-1.

[0051] [Table 1]

[0052] Table 1 shows that for the resin films of Examples 1 to 8, the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C is 0.2 or higher, indicating excellent impact resistance across the entire temperature range from 0°C to 60°C.

Claims

1. A resin film with a thickness of 150 μm, in which dynamic viscoelasticity measurements are performed in tensile mode at a vibration frequency of 100 Hz and a temperature range of 0°C to 60°C, and the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C is all 0.2 or greater.

2. The resin film according to claim 1, wherein the haze is 0.01% or more and 2.0% or less.

3. A resin film according to claim 1 or 2, for use in a foldable device.

Citation Information

Patent Citations

  • Front plate for foldable device and foldable device

    JP2024062966A

  • Adhesive-layer-equipped elastic sheet, and flexible display device in which same is used

    WO2022181656A1